Sleep disordered breathing and neurobehavioral deficits in children and adolescents: a systematic review and meta-analysis - Weiyu Zhang; Yubin Shen; Xiwen Ou; Hongwei Wang; Song Liu (BMC, 2024)
Abstract Background Sleep disordered breathing (SDB) is broadly recognized to be associated with neurobehavioral deficits, which have significant impacts on developing-aged children and adolescents. Therefore, our study aimed to quantify the proportion of neurobehavioral impairments attributed to SDB in general children and adolescents by population attributable fraction (PAF). Methods The study was registered at PROSPERO (ID: CRD42023388143). We collected two types of literature on the prevalence of SDB and the risk of SDB-related neurobehavioral deficits from ten electronic databases and registers, respectively. The pooled effect sizes (Pe, Pc, RR) by random-effects meta-analysis were separately substituted into Levin's formula and Miettinen's formula to calculate PAFs. Results Three prevalence literature and 2 risk literature, all with moderate/high quality, were included in the quantitative analysis individually. The prevalence of SDB was 11% (95%CI 2%-20%) in children and adolescents (Pe), while the SDB prevalence was 25% (95%CI 7%-42%) in neurobehavioral patients (Pc). SDB diagnosis at baseline was probably associated with about threefold subsequent incidence of neurobehavioral deficits (pooled RR 3.24, 95%CI 1.25-8.41), after multi-adjustment for key confounders. Up to 19.8% or 17.3% of neurobehavioral consequences may be attributed to SDB from Levin's formula and Miettinen's formula, respectively. Conclusions A certain number of neurobehavioral consequences may be attributable to SDB. It is essential for clinicians to identify and treat SDB timely, as well as screen for SDB in patients with neurobehavioral impairments. More longitudinal studies of SDB and neurobehavioral deficits are needed in the future to further certify the association between them.